KENDALA PANDEMI COVID-19 TERHADAP PROSES PEMBELAJARAN ONLINE DI MIN 4 BUNGO - N, Nurdin (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
Pademi covid-19 has disrupted the conventional learning process. So a solution is needed to answer these problems. Online learning is one alternative that can solve this problem. The research objective was to determine the obstacles faced by teachers, students and parents when teaching online at MIN 4 Bungo. This research method uses a qualitative case study, which is used to obtain information about the problems formulated by the author. Data collection techniques which include; Online observations and interviews. Respondents needed in this study were students and parents of class V at MIN 4 Bungo, totaling 30 people. The main obstacle faced is the lack of facilities owned by students when studying online because not all students have smartphones or computers as learning media used online. Apart from that, another obstacle is the internet package that cannot be reached by all students. The lack of knowledge about the use of technology and the considerable expenditure are obstacles to the learning process.